Whole Transcriptome Analysis Reveals a Potential Regulatory Mechanism of LncRNA-FNIP2/miR-24-3p/FNIP2 Axis in Chicken Adipogenesis - Guo, Lijin; Chao, Xiaohuan; Huang, Weiling; Li, Zhenhui; Luan, Kang; Ye, Mao; Zhang, Siyu; Liu, Manqing; Li, Hongmei; Luo, Wen; Nie, Qinghua; Zhang, Xiquan; et al. (Frontiers in Cell and Developmental Biology, 2021)
Lipid biosynthesis is a complex process, which is regulated by multiple factors including lncRNA. However, the role of lncRNA in chicken abdominal fat accumulation is still unclear. In this research, we collected liver tissues from 6 high abdominal fat rate Sanhuang broilers and 6 low abdominal fat rate Sanhuang broilers to perform lncRNA sequencing and small RNA sequencing. A total of 2,265 lncRNAs, 245 miRNAs and 5,315 mRNAs were differently expressed. Among of them, 1,136 differently expressed genes were enriched in metabolic process. 36 differently expressed genes, which were considered as differently expressed lncRNAs’ targets, were enriched in metabolic process. In addition, we also found that 8 differently expressed miRNAs could target to 19 differently expressed genes. FNIP2 and PEX5L were shared in cis-regulatory network and differently expressed miRNA target relationship network. LncRNA-FNIP2/miR-24-3p/FNIP2 axis was considered as a potential candidate that may participate in lipid synthesis. Experimentally, the objective reality of lncRNA-FNIP2/miR-24-3p/FNIP2 axis was clarified and the regulation effect of lncRNA-FNIP2/miR-24-3p/FNIP2 axis on synthesis was validated. In brief, our study reveals a potential novel regulatory mechanism that lncRNA-FNIP2/miR-24-3p/FNIP2 axis was considered as being involved in lipid synthesis during chicken adipogenesis in liver.